PENGARUH ZAKAT DAN INFAQ TERHADAP PENURUNAN KEMISKINAN DI ACEH PERIODE 2007-2017 - Afifudin, Toha; Sari, Nurma (JURNAL EKONOMI DAN BISNIS ISLAM, 2019)
The purpose of this study was to test the impact of zakat and infaq distribution collectively or partially against poverty alleviation in the Aceh province, Indonesia. This research is using statistical data from Badan Pusat Staistik (BPS) and Baitul Mal Aceh with a period of research 2007-2017. The methodology used in this research is descriptive quantitative and test multiple linear regression was used to test the infl uence of zakat and infaq decline of poverty in Aceh with t-test and f-test. results t statistics i.e. zakat partially to decrease poverty in Aceh while the Infaq partially has no effect against a decline in poverty in Aceh. Multiple linear regression test results simultaneously zakat and infaq eff ect on decreasing poverty in Aceh.